Technology Adoption in Education: Usage, Spillovers and Student Achievement - Peter Leopold S. Bergman (Center for Economic Studies and ifo Institute (CESifo), 2016)
Given significant expenditures on education technologies, an important question is whether these products are adopted by their end users and are effective in practice. This paper studies the adoption, diffusion, and effects of one type of technology that is increasingly ubiquitous: school-to-parent communication technologies. Using data from a Learning Management Sys-tem in several hundred schools and a two-stage experiment to study the adoption of this technology by parents, I find: A quarter of parents ever use it; adoption follows an S-shape; significant spillovers occur along intensive but not extensive margins; and there is evidence student grades improve as a result.
Keywords: I20; 330; education; technology adoption